PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH PADA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 14 MERANTI - Syahpitri , Rahmadhani; Sari, Rani Permata; Ria Azhari (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2022)
The make a match cooperative learning model in reality has not been optimally applied by Islamic religious education teachers at SDN 14 Meranti in class. At the time of applying this method there were some students who were active and some students who were not active,this caused learning to be not optimal because not all students were active in learning. The learning process causes not all students to be able to build their knowledge, attitudes and skills so that the learning outcomes are less than optimal. The approach that will be used inthis study is a descriptive qualitative approach, because this research emphasizes its analysis on deductive and inductive inference processes and analysis of the dynamics of the relationship between observed phenomena, using scientific logic. This type of research isfield research, namely research where data collection is carried out in the field, such as in the community, community organizations and institutions, and educational institutions. This research will be conducted at SDN 14 Meranti. The application of the make a match type of cooperative learning model in learning Islamic religious education in class III at SDN 14 Meranti succeeded in increasing student activity in learning. This learning model also helpsstudents build knowledge, attitudes and skills so that learning outcomes become optimal and the learning process becomes enjoyable.